Reading sources in English to write a literature review in a romance language: a genre-based eap course in a masters program - Martínez, Iliana; Picchio, Romina (The ESPecialist, 2015)
This article describes a genre-based, field-specific EAP course offered in a Latin American university to Master’s candidates of veterinary science who are in the process of writing literature reviews for their dissertations. As their dissertations are expected to be novel contributions, the writers need to have access to scientific information in English, although the final product will be produced in their native Romance language, Spanish. To meet this need, we capitalized on the advantages of the context, particularly the common L1 background and the field homogeneity of the course group, thus allowing for specific instruction.